Early Cretaceous Volcanism in Central and Eastern Argentina During Gondwana Break-Up - Lagorio, Silvia Leonor; Vizán, Haroldo; Geuna, Silvana Evangelina (SpringerBriefs in Earth System Sciences, 2016)
This book analyzes the Early Cretaceous volcanic processes in Misiones Province and in Sierra Chica de Córdoba (Argentina). The volcanism in Misiones is tholeiitic and belongs to the Parana Magmatic Province (PMP), which extends throughout South America. In contrast, the volcanism in Córdoba is geographically restricted and of alkaline nature, representing a potassic locality peripheral to the PMP. To understand the causes of and geodynamic processes involved in these volcanisms, a new 40Ar /39Ar of 129.6 ± 1 Ma of a trachyte from Sierra Chica de Córdoba is presented. This dating points out that the volcanism in Sierra Chica de Córdoba slightly postdates PMP lavas. Moreover, complementary geochemical analyses from Misiones Province are presented and compared with those from the whole PMP in order to characterize its source.